PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PAI PESERTA DIDIK DI MTS NEGERI TAMBUN TOLITOLI - Wahyuni, Ni’mah (Musawa: Journal for Gender Studies, 2022)
This paper discussed the influence learning motivation to the students learning achievement of islamic education. The objectives of this research; (1) to find out partially whether the motivasi of parents and learning have influence on the students learning achievement of islamic education.(2) to determine partially whether the learning motivation have influence on students learning achievement of islamic education. This research was a quantitative research design through Ex-Post Facto approach. The samples of the research were 75 respondents. It was selected by applying stratified random sampling techniques. Data collection was gathered by using some instruments;observation, questionnaire and documentation which using multiple regression test. The result of partial test of the students learning motivation to the students learning achievement found tcounted 5,346> ttable 1.99 and level of significance was less than the level of mistrust 5% (0.000 <0.05). It partially meant that the variable of the students learning motivation have a significant positive influence on the students learning achievement of Islamic education. In conclusion, the more increase the students learning motivation and the more increase the students learning achievement of Islamic education. The result of this research is expected to be useful effect and give positive contribution for education especially in islamic course.